Wpływ wybranych nowoczesnych technologii na zdrowie studentów = Influence of selected new technologies on the health of college students - Babula, Mateusz; Warchoł, Martyna; Kowalczyk, Anna (Journal of Education, Health and Sport, 2016)
Babula Mateusz, Warchoł Martyna, Kowalczyk Anna. Wpływ wybranych nowoczesnych technologii na zdrowie studentów = Influence of selected new technologies on the health of college students. Journal of Education, Health and Sport. 2016;6(7):429-438. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.58512 http://ojs.ukw.edu.pl/index.php/johs/article/view/3706 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 21.07.2016. Wpływ wybranych nowoczesnych technologii na zdrowie studentów Influence of selected new technologies on the health of college students Mateusz Babula1 Martyna Warchoł2 Anna Kowalczyk2 1Uniwersytet Technologiczno–Humanistyczny w Radomiu 2Uniwersytet Medyczny w Lublinie Mateusz Babula1 Mgr Martyna Warchoł2 Mgr Anna Kowalczyk2 1Uniwersytet Technologiczno–Humanistyczny w Radomiu 2Uniwersytet Medyczny w Lublinie Streszczenie: Wstęp: Dostępność telefonów komórkowych oraz Internetu stała się przyczyną pojawienia się nowych zachowań w życiu codziennym oraz nowych sposobów komunikowania się. Nasilił się również kontakt z telefonem jako takim - rozmawiamy coraz częściej nie tylko w celu przekazania informacji, ale także dla przyjemności. Można mieć go zawsze przy sobie, używać wszędzie i w każdej chwili, co sprawia, że jest się zawsze uchwytnym. Natomiast długotrwałe korzystanie z telefonu, komputera i Internetu może nieść za sobą niepożądane skutki zdrowotne. Cel pracy: Praca ma na celu zbadanie wiedzy studentek na temat wpływu nowoczesnych technologii takich jak komputer, telefon i Internet na zdrowie. W niniejszej pracy starano się ocenić, czy studenci mają świadomość jak na zdrowie wpływa używanie komputera, telefonu i Internetu. Starano się również określić, jaki wpływ na zachowania zdrowotne mają nowoczesne technologie oraz jakie dolegliwości występują w związku z korzystaniem z nich. Materiał i metody badawcze: W badaniu zastosowano metodę sondażu diagnostycznego. Ankieta miała charakter anonimowy, udział w niej był całkowicie dowolny. Grupę badaną stanowiło 100 studentów w tym 74% kobiet i 26% mężczyzn. Większość z nich mieszkała na wsi (69%). Badania odbywały się na zasadzie anonimowości. Ankiety zostały wysyłane do respondentów za pomocą Internetu. Wyniki i Wnioski: Najczęściej z nowoczesnych technologii korzystamy w domu. Największa ilość respondentów używa nowoczesnych technologii przez 2 do 4 godzin dziennie. 54% respondentów nie wyobraża sobie bez nich życia. Użytkowanie komputera, telefonu i Internetu powoduje brak ruchu, brak czasu oraz jedzenie przed komputerem. Podczas siedzenia przed komputerem 70% respondentów nie zwraca uwagi na postawę ciała. Najczęstszymi dolegliwościami związanymi z korzystaniem z nowoczesnych technologii są ból mięśni i kręgosłupa oraz zaczerwienienie i ból oczu. Słowa kluczowe: nowoczesne technologie, zdrowie, komputer, telefon, Internet. Background: The availability of mobile phones and the Internet has become the reason for the emergence of new behavior in everyday life and new ways of communicating. Intensified also in contact with the phone as such - we are talking more and more often, not only to provide information, but also for pleasure. You can have it always with you, use anywhere and at any time, which makes it always perceptible. In contrast, long-term use of telephone, computer and the Internet may have some adverse health effects. Aim: To work is to investigate the knowledge of students about the impact of modern technology such as a computer, telephone and Internet health. In the present study sought to assess whether students are aware of how health affects the use of a computer, telephone and Internet. Efforts were also made to determine the impact on health behavior have modern technologies and what problems exist in connection with the use of them. Material and research methods: The study used diagnostic survey method. The survey was anonymous, the participation in it was completely arbitrary. A group of consisted of 100 students including 74% of women and 26% men. Most of them lived in rural areas (69%). Research is carried out on an anonymous basis. Surveys were sent to respondents via the Internet. Results and Conclusions: The most modern technology we use at home. The largest number of people use modern technology for 2 to 4 hours per day. 54% of respondents not imagine life without them. Using the computer, phone and the Internet causes a lack of exercise, lack of time and the food in front of a computer. When sitting in front of a computer 70% of respondents did not pay attention to posture. The most common symptoms associated with the use of modern technology are muscle pain and spine as well as redness and eye pain. Keywords: modern technologies, health, computer, phone, internet.